Causes and corrections of corneal ulcer in pet animals – Literature review (Research, Society and Development, 2021)
Recently, ophthalmology has progressively grown in veterinary medicine, resulting in new discoveries of causes and treatments. Corneal Ulcer is the rupture of the epithelial membrane and the appearance of the stroma, which is stained with sodium fluorescein, used for diagnosis of the disease. It has several conditioning factors for the occurrence. This literature review aims to reinforce to students and veterinary clinicians the causes of corneal ulcers, the most suitable therapy for each case and list the possible treatments and define them. The present study involves corneal ulcer treatment techniques. Articles in databases from 2006 to 2021 were used, in addition to consultations in veterinary ophthalmology books. The animal with corneal ulcer must undergo a complete, specific and complementary clinical examination, it is recommended to perform culture and antibiogram to adjust the therapy. It is up to the clinician to investigate the predisposing factors and the best treatment, in the same way, the surgeon must determine the best technique according to his own indications and abilities. New treatments need more studies on applicability. But surgical treatments generally remain safe and effective, especially in severe cases.